INGLIZ TILINI O’QITISHDA YOZMA TILNI RIVOJLANTIRISH UCHUN KOMMUNIKATIV USULNI QO’LLASH - Habibnazarova, S. (SCIENCE and SOCIETY, 2021)
The given article deals with the writing strategies in teaching English. Writing is one of the four language skills: reading, writing, speaking and listening. Writing is considered to be productive skill that means, it involves producing language rather than receiving it. There are given main stages of writing, seven ways of correction and teachers’ tasks.